Community-Based Disaster Risk Management through the Disaster-Resilient Village Program at the Regional Disaster Management Agency of Pesisir Selatan Regency - Bakhtiar, Riswanto; Takdir, M.; Sepriani, Ririn (The Future of Education Journal, 2026)
This research is motivated by disaster risk management based on disaster-resilient villages in the Pesisir Selatan district. The study aims to understand how the Destana community and the Regional Disaster Management Agency (BPBD) manage disaster risks in Pesisir Selatan. This research uses a qualitative method that describes the results of community-based disaster risk management in Pesisir Selatan, including the challenges and efforts in managing disaster risks. The sampling technique used is purposive sampling. The results indicate that disaster risk management in Pesisir Selatan emphasizes that the effectiveness of disaster response heavily relies on systematic communication and education for the community. Through the Disaster-Resilient Village program, this strategic approach not only builds community capacity to face disaster risks but also strengthens collaboration between the government and related agencies. The award from BNPB to Painan Selatan demonstrates the positive potential of this program. Additionally, the use of social media for communication and coordination between BPBD and disaster-resilient villages allows the community to remain vigilant against potential threats. The establishment of disaster- resilient village communities also requires active participation from all layers of society in organization and decision-making, reflecting that disaster risk reduction is a shared responsibility, not just the government’s. However, there are still challenges faced by the local government, including budget shortages, community understanding, and a lack of resources in the regional disaster management agency. Nevertheless, the government has made several efforts, including allocating village budgets, advocating, and continuously providing education to the community.